A Pilot Study of Core Topics in Introductory Social Psychology and Developmental Psychology Textbooks. (January 2014) - Whitehead, George I.; Smith, Stephanie H.; Losonczy-Marshall, Marta
This study examined the similarities and differences in the topics and references in selected chapters of eight introductory social psychology textbooks and six developmental psychology textbooks. We wanted to determine the extent to which there were core concepts and references presented in these chapters. We found a relatively small set of core topics and references in all of the selected chapters, indicating a lack of consensus among textbook authors as to the core concepts and references in the topic areas. These findings have implications for scholarly agreement about the knowledge base of psychology and the assessment of it.